Assessment of knowledge among ASHAs in the delivery of contraceptive information and services in coastal Andhra Pradesh - Palla, Jayasree; Komaram, Ravi Babu (International Journal Of Community Medicine And Public Health, 2020)
Background: Government of India (GOI) is providing comprehensive integrated health care to the urban and rural people under the umbrella of National Health Mission. ASHA as an activist, a village level community health worker acts as an interface between the community and the public health care delivery system, and plays a central role in achieving population policy goals. The aim of study was to assess the knowledge component of ASHAs in the delivery of contraceptive information and services in coastal Andhra Pradesh. Methods: A descriptive cross-sectional study was conducted in East Godavari district of Andhra Pradesh at sub-centres among 170 ASHA workers. The study area was selected by multi stage sampling technique. Data was collected using pre tested, semi-structured interview schedule. Qualitative data was expressed in percentages, and quantitative data was expressed in mean and standard deviation. Results: The mean age of ASHAs was 28.4 years (SD±3.82). Majority (75.88%) of ASHAs had completed secondary level education, 72.94% had knowledge regarding contraception for newly married couple, and 68.23% were aware of the effective time period for intake of emergency contraceptive pills. 45.88% of ASHAs were unaware of safe period. Conclusions: Majority of ASHAs had knowledge in certain areas of contraceptive information and services, whereas some are lacking knowledge regarding safe period, emergency contraceptive pills (EC pills), progesterone only pills, missed pills and period of condom use after vasectomy. Hence, it is essential to ensure that they receive quality training on contraceptive information and services from qualified personnel at regular intervals.